Kontribusi Agility Terhadap Kemampuan Dribbling Permainan Sepakbola Di Club Suguh Fc Seluma - Husnul, Muhammad Aldo Ikhsan; Anggara, Deffri; Lismana, Oetari (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the contribution of agility to dribbling ability in soccer games at Club Suguh FC Seluma. This type of research is correlational research. The research sample amounted to 30 people. The instrument used in this study was the Ilionis agility test to measure dribbling ability in soccer games. Where the results of research and discussion, the researcher concluded that of the 30 people at Club Suguh Fc Seluma who had Agility in soccer games as many as 3 people (10%) had a Good category. A total of 10 people (33%) have a Medium category. A total of 8 people (27%) have a Lack category and a total of 9 people (30%) have a Very Lack category. Then continued again with the Dribbling Ability test which was attended by 30 people at Club Suguh Fc Seluma having Dribbling Ability as many as 14 people (47%) had a Good category. As many as 4 people (13%) have a Medium category and as many as 12 people (40%) have a Very Poor category. From all the research tests carried out such as Agility and Dribbling Ability carried out at Club Suguh Fc Seluma it can be concluded that: Agility and Dribbling Ability tests obtained rtabel of 0.361 because the correlation coefficient between rxy = 0.82> 0.361 and a contribution of 67.24% which means that the Contribution of Agility and Dribbling Ability tests in Soccer Games at Club Suguh Fc Seluma is significant and large.